Extraction of Sarawak black pepper essential oil using supercritical carbon dioxide - Kumoro, A.C.; Hasan, M.; Singh, H. (Springer Verlag (Germany), 2010)
Black pepper (Piper nigrum L.) essential oil has been widely used as a warming and energizing oil that is helpful at the onset of respiratory infections, and for soothing muscular aches and pains. Extraction of essential oil using conventional techniques has considerable limitations, such as low extracting power and selectivity, possibility of solvent contamination, degradation of thermally labile product, and environmental problems. The supercritical fluid extraction (SFE) of essential oil from ground black pepper using supercritical carbon dioxide as a solvent is presented in this study. The effect of process parameters, namely pressure (7.5, 10, and 15 MPa), temperature (303, 313, and 323 K) and particle size (0.5 mm, 0.75 mm, and whole berries), on the extraction rate was examined in a series of experiments conducted in a laboratory scale apparatus. The essential oil obtained from supercritical carbon dioxide extraction contained higher levels of sequiterpene hydrocarbons, leading to higher sesquiterpene to monoterpene ratios as compared to that obtained from hydro distillation. The results showed an increase of extraction rate with the increase of pressure or temperature. In contrast, the increase of particle size reduced the extract yield and extraction rate.